Strategy Integrated Learning Through The Model of Deep Discussion Group Activities (DMKK) Based on Local Wisdom as Efforts for Establishing Characters of JHS Students - Rohmatillah, Septya; Budiarso, Aris Singgih (PSEJ (Pancasakti Science Education Journal), 2019)
Education is an effort to educate the life of the nation. Operationally, education in the process through learning with the output of learning outcomes in the realm of knowledge, skills, and attitudes in this regard is related to the character that has become the problem of the Indonesian nation. With these conditions, the building of student character is needed in the millennial era, especially to build students' readiness in facing the challenges and developments in science and technology. Character building through the learning process can be done by using strategies integrated learning through-based DMKK models local wisdom. The chosen strategy integrated learning aims to have students have a learning experience from various sources with different perspectives so that students get a thorough thinking about a problem and can solve various problems. Through the DMKK model, the teacher does not have to be fixated on the steps of a particular learning model and the teacher is more flexible in teaching and learning activities and the use of media or tools available in the classroom. The DMKK model can provide opportunities for students to think deeply about a problem faced. The use of local wisdom in learning is able to provide experiences directly to students in accordance with the potential of the surrounding area. The method used in this is a study literature study on various related sources. The results of this study are expected to provide solutions related to the utilization of regional potential as a source of learning through an in-depth mindset so as to provide opportunities for students to solve problems from various perspectives while still having positive character.